A comparison of oral and implant naltrexone outcomes at 12 months - Colquhoun, BPsych(Hons), Ross; Tan, MBBS, Donald Y-K.; Hull, BPsych(Hons), Samantha (Journal of Opioid Management, 2005)
Naltrexone’s current use has been limited by compliance. Subcutaneous implants would seem to offer a solution to this problem and improve long-term outcomes. The aim of the present study was to compare groups of patients who had received oral naltrexone or a naltrexone implant after detoxification and to follow their progress. Forty-one patients received an implant, and 42 patients received oral naltrexone. They were surveyed at one, three, six, and 12 months after detoxification. Their designated support person was also contacted to confirm the self-reports of the participants. Patients were compared on gender, age, and length of time since detoxification. Implant patients showed much higher abstinence rates, while those in both groups who were abstinent showed greater compliance to naltrexone (time spent in treatment) and attended more counseling sessions. Although the participants were not randomly allocated to each treatment condition, the preliminary evidence indicates that implants can improve compliance rates and outcomes.